Stigma and social support and their impact on quality of life and self-esteem among women with endometriosis in Latin-America and the Caribbean. - Yatzmeli Matías-González; Astrid Sánchez-Galarza; Ernesto Rosario-Hernández; Idhaliz Flores-Caldera; Eliut Rivera-Segarra (PLOS Global Public Health)
Endometriosis is a complex disease affecting approximately 5-10% individuals worldwide. Prevalence rates in Latin-America and the Caribbean are largely unknown, with published data only from Puerto Rico and Chile. Pain associated with endometriosis negatively affects patients' health and quality of life. However, there is a need to better understand the role played by psychosocial variables such as stigma and social support in diverse cultural contexts. The purpose of this study was to examine the mediating role of endometriosis related stigma (endo-stigma) and the moderating role of social support on the endometriosis QoL and self-esteem among women with endometriosis from Latin America and the Caribbean. A cross-sectional design with online survey techniques was implemented. A total of 169 self-identified cisgender women with endometriosis from 14 Latin-American and Caribbean countries participated in the study. We used partial least squares structural equation modeling (PLS-SEM) to examine the study's hypotheses. Incapacitating pain was positively and significantly related to endometriosis QoL as measured by the EHP-5 (b = .266, p < .01). Endo-stigma was positively and significantly related to endometriosis QoL (b = .340, p< .01) and self-esteem (b = .297, p< .01). In addition, endo-stigma mediated the relationship between incapacitating pain and self-esteem (IE = .073, p = .018). Finally, social support moderated the relationship between stigma stress and endometriosis QoL (b = .060, p = .039). Findings suggest stigma could be one of the mechanisms through which the relationship between incapacitating pain and self-esteem among Latin American and Caribbean women with endometriosis could be partially explained. Furthermore, women who scored high in the need for social support and stigma stress also showed worst endometriosis QoL. These results point towards the need to develop tailored interventions targeting these factors in order to foster a better QoL and wellbeing for this population in the context of Latin America and the Caribbean.